EFFECT OF STORAGE ENVIRONMENT AND PACKAGING MEDIA ON THE DISEASE INCIDENCE AND WEIGHT LOSS OF STORED AFRICAN STAR APPLE (Chrysophyllum albidum) - Sunmonu, M. O.; Odewole, M. M.; Obajemihi, O.; Ajala, O. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2017)
A study was conducted to study the effect of storage environment and packaging media on the disease incidence and weight loss of stored African Star Apple (Chrysophyllum albidum). Three storage environments were identified in this study namely- evaporative cooling basket, refrigerator and ambient storage and freshly harvested ripe African star apples were wrapped in perforated polythene, moist jute material and without packaging and stored under these three storage environment. The apples were observed for deteriorations mediated by microbial infection and insect infestation. Manifestation of infestation which affected the shelf-life of African Star Apple was delayed most in the refrigerator. The level of infestation of the apples stored in evaporative cooling basket was next to the refrigerator in the decreasing order. Weight losses were lower in apples wrapped with moist jute sack (0.48% ± 1.6) stored in refrigerator than those wrapped with perforated polythene (0.79% ± 1.2) and unwrapped (1.45% ±1.4). Similar wrapping effects were obtained in the evaporative cooling basket and ambient. Weight losses were lower in apples stored in refrigerator (0.91%) than in the evaporative cooling basket (2.84 %) and ambient shade (7.41 %).